Ecology of Shipwrecks Around Mauritius Island: Implications for Optimizing Shipwreck Performance for Marine Biodiversity - Marwyn Anasamy; Brihatee Mattapullut; Homesha Bhurosah; Vasisht Seetapah; Ashfaaq Muhammad Korimbocus; Kamakshi Ramkalam; Ranjeet Bhagooli; Shakeel Yavan Jogee; Deepeeka Kaullysing (Marine Ecology, 2026)
Shipwrecks can function as artificial reefs that enhance marine biodiversity and productivity by providing structurally complex habitats. However, ecological assessments of shipwrecks in the Western Indian Ocean, including Mauritius Island, remain scarce. This study presents the first systematic ecological evaluation of five shipwrecks around Mauritius, focusing on their ecological performance in terms of fish assemblages and benthic composition, and identifying environmental thresholds that favour biodiversity enhancement. Belt transects (2 m × 1.5 m) laid across the full width of each wreck were used to quantify fish assemblages, while benthic cover was assessed using line intercept transects. Environmental parameters including light, depth, temperature, dissolved oxygen, pH, salinity, and nutrient concentrations were recorded at each site. Fish biomass and community composition varied significantly among wrecks, with the highest mean biomass (138.6 ± 13.2 g m −2 ) and density recorded at shallower, well‐illuminated, structurally degraded wrecks. In contrast, coral cover peaked (21.9% ± 3.9%) on structurally intact wrecks under similar light regimes. Linear mixed‐model analysis identified light availability and pH as key drivers of fish biomass, while structural integrity supported coral cover. Principal Coordinates Analysis (PCoA) further indicated that depth, nitrate, and pH were key factors structuring both coral and fish assemblages. Building on these patterns, an exploratory framework termed the Optimal Ecological Performance Thresholds (OEPT) was derived to identify indicative environmental and spatial ranges representing conditions that can maximize coral cover and fish biomass. These thresholds provide a preliminary, science‐based reference for guiding future shipwreck deployments and ecosystem‐based coastal management.